Anti democratic attitudes: The influence of work, digital transformation and climate change - Andreas Hövermann; Bettina Kohlrausch; Dorothea Voss-Dahm (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2022)
When anti-democratic attitudes find great popular acclaim, it is time to sit up and take notice: people are turning away from the democratic system and no longer put their trust in the political and social rules and instances that organise and structure societal coexistence. As a result, social cohesion and the acceptance of democratic decisions come under increasing pressure. And yet a stable democracy is particularly important at a time in which the "three Ds" - decarbonisation, digitalisation, demography - are challenging German society and triggering change. So how widespread are anti-democratic attitudes and how is the connection between social circumstances and democratic integration during times of announced and actual change processes? How do perceptions and experience resulting from gainful employment influence anti-democratic attitudes? We have taken the evaluations of a representative public opinion poll to show that people in objectively precarious circumstances are denied access to opportunities for participation and for shaping their own lives also in view of external changes. Subjective perception also plays a role in anti-democratic attitudes: the lack of recognition is experienced as devaluation of one's own social and professional status. Anti-democratic attitudes are also closely linked to the fear and experience of getting left behind by social change processes such as digital or socioecological transformation.
Keywords: 330